Вибір оптимальної конфігурації програмного забезпечення навчальних лабораторій для проведення практичних занять та лабораторних робіт із дисципліни ОС UNIX. - Сокорчук, І. П. (ХНУРЕ, 2016)
This paper discusses software requirements for practical and lab classes in the OS UNIX university course. The criteria are stated for software choice and some possible software configurations are considered. It was found the conformity of specified criteria. The most suitable software was selected. The author defined software configuration for OS Unix laboratories with client-server network architecture and fat (rich) client GNU/Linux workstattions. The author provides detailed discussion of the software for developing such a system. A description of a pilot implementation of the system concluds the paper.
Keywords: UNIX; Linux; клієнт-сервер; fat client; rich client; LTSP